Answer: p = 6
Step-by-step explanation: To solve this equation, we start by distributing the 9 through the parentheses on the left side.
So we have 9 times p which is 9p - 9 times -4 which is -36. So our equation now reads 9p - 36 = 18. Solving from here, we want to add 36 to both sides of the equation to get 9p = 54. Then divide both sides by 9 to get p = 6.
To check our answer, we can substitute a 6 back in for p in the original equation which gives us 9 (6 - 4) = 18 or 9 (2) = 18 or 18 = 18 which is a true statement so we know our answer is correct.